Careers Certification Uncertainty. - Karlin, S.
This paper discusses whether professional certificates are worth the time and expense. Altough having a certification does confirm proficiency in certain technologies, it isn't enough to make a viable candidate - work experience is also needed. On the other side, having a certification can be important. Certification popularity changes according to technology demands. Overall, the big downside of certification is that, to stay current, you have to come home and study for 1 to 4 hours
Keywords: Certification; Information technology industry; Professional certificates; Technology proficiency